Integrasi Resolusi Konflik ke dalam Pembelajaran: Guru sebagai Agen Perdamaian dalam Pendidikan di Sekolah Kejuruan - Eva Imania Eliasa; Ilfiandra; Suwarjo; Sahril Buchori; Nadia Aulia Nadhirah; Afanin Halqim; Fayruziyah Ifroch Sabtana; Sarah Salsabila (Universitas Islam Negeri Madura, 2026)
Peace education can equip students with various skills to participate meaningfully in a democratic society. One of the skills that can be developed is peaceful conflict resolution. This research examines the role of teachers in developing a culture of peace through conflict resolution practices in the environment of Vocational High School. The method used is qualitative with a phenomenological model, involving 5 teachers who have received training in peace education implementation. The research results show that the values of peace have been integrated into various subjects through the teachers' concrete actions, especially in the form of self-regulation, interpersonal skills, and communication skills. The teachers demonstrated the ability to manage emotions, avoid and resolve conflicts, and create a peaceful and harmonious school environment. This research emphasizes the importance of conflict resolution education in the school curriculum to improve the quality of student interactions and reduce conflicts in schools. The findings of this study encourage the need to evaluate teaching materials so that peace values are clearly emphasized in the learning process, enabling schools to become strategic spaces for building a sustainable culture of peace.